Multiclass emerging organic pollution and associated risks in the Klang River estuary in Malaysia - Tuan Omar, Tuan Mohamad Fauzan (2018)
The occurrence, distribution and sources of multiclass emerging organic contaminants (EOCs) in the environmental matrices (estuarine water, sediment and biota) from Klang River estuary were examined. The targeted EOCs for this assessment were endocrine disrupting compounds (bisphenol A, 4-0P, 4-NP, E2, El and EE2), organo phosphorous pesticides (quinalphos, chlorpyrifos, diazinon) and pharmaceutically active compounds (primidone, su1famethoxazo1e, dexamethasone, diclofenac, amoxicillin, progesterone, testosterone). Analytical methods of quantification for determination of multi class EOCs were developed for three components of environmental matrices, namely estuarine water, sediment and biota matrices. The developed analytical methods were validated for linearity, extraction efficiency (% recovery), precision, method detection limit as well as matrix effects. Satisfactory optimization were achieved for the developed analytical methods with extraction efficiency between 51 to 126%, as well as excellent linearity (r > 0.991) and precision (%CV < 20). Results from this field study showed that prevalent contamination of Klang River estuary by EOCs with several compounds such as diclofenac, bisphenol A, progesterone, estrone and amoxicillin were predominantly detected in the three environmental matrices. For estuarine water samples, bisphenol A was the compound mostly detected, contributed about 54.77% of total concentration followed by amoxicillin (39.17%), estrone (2.16%) and diclofenac (1.67%). The highest concentration ofEOCs in surface water samples was found in BPA at 597.30 ng/L, followed by amoxicillin at 102.31 ng/L. While for sediment samples, bisphenol A was the highest concentration detected at 16.84 ng/g followed by diclofenac (13.88 ng/g) and estrone (12.47 ng/g). The percentage of contribution (% of total concentration) is in order of bisphenol A (49.68%), diclofenac (16.19%), progesterone (10.37%) and El (9.25%). As for biota matrices, diclofenac (10.76 ng/g) was detected at the highest concentration in fish samples, while progesterone (9.57 ng/g) was the highest concentration found in the molluscs. Principal component analysis (PCA) has successfully extracted four principle components, revealing that the sources ofEOCs in the estuary originated from water/waste treatment plants, medical waste discharges, industrial pollution and aquaculture/livestock activities. Estimation of human health risk assessment, calculated as hazard quotient (HQ) were less than 1, suggesting the consumption of fish and mollusc from Klang River estuary will not pose any health 'risk to the consumers. Meanwhile, environmental risk assessment, expressed as risk quotients (RQs) for all targeted compounds were also less than 1 for the three test species (phytoplankton, zooplankton and fish) evaluated. Hence, the targeted EOCs have not indicated significant risks to the ecosystem during the current assessment. Nonetheless, result from this field assessment is an important finding for pollution studies in Malaysian tropical coastal ecosystems particularly for organic micro-pollutant EOCs and can also serve as a baseline database for future reference.